The Todaro Paradox Revisited - Yves Zenou (The Research Institute of Industrial Economics (IUI), 2005)
The Todaro Paradox states that policies aimed at reducing urban unemployment are bound to backfire: they will raise rather than reduce urban unemployment. The aim of this paper is to reexamine this paradox in the context of efficiency wage and search-matching models. For that, we study a policy that consists in decreasing the urban unemployment benefit. In an efficiency wage model, we find that there is no Todaro paradox while this is not always true in a search-matching model since a decrease in the urban unemployment benefit can increase both urban employment and unemployment.
Keywords: D83; J41; J64; O15; 330; Efficiency Wages; Search-Matching; Rural-Urban Migration; Policy; Effizienzlohn; Landflucht; Städtische Arbeitslosigkeit; Arbeitslosenversicherung; Theorie; Matching